Management of acute traumatic intracranial haematoma in rural and remote areas of Australia. Issue 1 (3rd May 2016) - Gilligan, John; Reilly, Peter; Pearce, Andrew; Taylor, Danielle
Abstract : Introduction: Outcomes are reviewed with traumatic brain injury (TBI) involving intracranial haematomata (ICH) with patients in rural and remote areas of South Australia and adjacent states. Patients were referred to the Royal Adelaide Hospital (RAH), a level 1 trauma centre with a major neurosurgical service. Method: From 2000 to 2013, 1107 multiple trauma cases included 162 with severe TBI. Local medical officers (LMOs) phoned a specific number to access resuscitative and neurosurgical advice. Onsite neurosurgical support was provided when requested. Specialist teams later retrieved these patients to RAH. Locations were coded according to the Accessibility/Remoteness Index of Australia (ARIA+). Injuries were coded using ICD 9 and 10. Results: General surgeon LMOs drained nine clinically progressive ICHs. Neurosurgical attendance was provided in four instances. Eight patients survived. The remaining 153 patients had other injuries involving thoraco‐abdominal organs, spine, pelvis and limbs. The overall mortality was 30%. Twenty‐six had ICHs requiring surgical drainage later at the RAH, with 46% mortality. Average Injury Severity Score was 30 (range 9–66). Male/female ratio was 76/24. Motor vehicular accidents predominated (60%), followed by falls (26%) and assaults (10%). Those under 30 years were overrepresented. Patients were transported a mean distance of 283 km (maximum distance 2600 km). Conclusion: LMOs in remote locations may consider immediate drainage of deteriorating traumatic ICH. Adequate support from a distant major trauma centre can help achieve acceptable outcomes. Effective communications are vital. The Royal Australasian College of Surgeons and Neurosurgical Society of Australasia guidelines based on the Early Management of Severe Trauma protocols can assist LMOs in making the decision to undertake emergency craniotomy.